PERBANDINGAN PENDAPATAN USAHATANI JAGUNG MANIS DAN JAGUNG BIASA DI DESA TONTALETE KECAMATAN KEMA KABUPATEN MINAHASA UTARA - Calvin N. Gifelem; Rine ., Kaunang; Eyverson ., Ruauw (AGRI-SOSIOEKONOMI, 2016)
This study aimed to determine and compare the average income from farming of sweet corn and regular corn in Tontalete village Kema District of North Minahasa Regency for one planting season. This research was conducted during the three months from April to June 2015, located in the village of Tontalete, District of Kema Minahasa Utara Municipality. The data were obtained using a questionnaire. Sampling was done in two stages. The first step is determining the sample villages in doing a purposive sampling. The second step is determining the farmers sampled using simple random sampling method. Number of samples of each farm by 15 farmer or a total of 30 farmers. The results showed that the income per hectare of sweet corn farming for Rp 52.950.800 higher than the regular corn farming income only amounted Rp 21.799.100. Total land area is in use by all corn farmers by 43 hectares consisting of 23.5 ha for sweet corn farming, or by an average of 1.6 ha per farmer and 19.5 ha for regular corn farming or by an average of 1.3 ha per farmer. Costs incurred in the regular corn farming is greater than the costs incurred in the farming of sweet corn.*er